Hydrophobic analogues of rhodamine B and rhodamine 101: potent fluorescent probes of mitochondria in living C. elegans - Mottram, Laurie F.; Forbes, Safiyyah; Ackley, Brian D.; Peterson, Blake R. (Beilstein Journal of Organic Chemistry, 2012)
Mitochondria undergo dynamic fusion and fission events that affect the structure and function of these critical energy-producing cellular organelles. Defects in these dynamic processes have been implicated in a wide range of human diseases including ischemia, neurodegeneration, metabolic disease, and cancer. To provide new tools for imaging of mitochondria in vivo, we synthesized novel hydrophobic analogues of the red fluorescent dyes rhodamine B and rhodamine 101 that replace the carboxylate with a methyl group. Compared to the parent compounds, methyl analogues termed HRB and HR101 exhibit slightly red-shifted absorbance and emission spectra (5–9 nm), modest reductions in molar extinction coefficent and quantum yield, and enhanced partitioning into octanol compared with aqueous buffer of 10-fold or more. Comparison of living C. elegans (nematode roundworm) animals treated with the classic fluorescent mitochondrial stains rhodamine 123, rhodamine 6G, and rhodamine B, as well as the structurally related fluorophores rhodamine 101, and basic violet 11, revealed that HRB and HR101 are the most potent mitochondrial probes, enabling imaging of mitochondrial motility, fusion, and fission in the germline and other tissues by confocal laser scanning microscopy after treatment for 2 h at concentrations as low as 100 picomolar. Because transgenes are poorly expressed in the germline of these animals, these small molecules represent superior tools for labeling dynamic mitochondria in this tissue compared with the expression of mitochondria-targeted fluorescent proteins. The high bioavailabilty of these novel fluorescent probes may facilitate the identification of agents and factors that affect diverse aspects of mitochondrial biology in vivo.
Keywords: Caenorhabditis elegans; chemical biology; fission; fluorophores; fluorescence; fusion; imaging; in vivo; microscopy; mitochondria; model organisms; organelle; rhodamine; spectroscopy